Perancangan Ulang UI/UX Pada Website Diva Clinic Menggunakan Metode Design Thinking - Febrianti Setya N, Adelina; Umam, Khoirul; Nuansa Ratri, Indira; Hakim, Lutfi; Suwardiyanto, Devit (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2024)
The rapidly growing beauty industry has made beauty clinics such as Diva Clinic in Banyuwangi a top choice for individuals seeking optimal skin care. Diva Clinic actively promotes and provides information through social media and its official website. However, Diva Clinic faces challenges in optimizing its website, particularly regarding information presentation, cluttered layout, and monotonous color schemes. This study aims to redesign the Diva Clinic website to be more efficient and appealing to visitors. By applying the Design Thinking method, this research analyzes existing features and tests usability using the System Usability Scale (SUS). The prototype design, developed using the Design Thinking method, yielded recommendations validated through SUS testing, which showed a final score of 81.33, classified as grade A in the excellent category. This is significantly higher than the previous score of 52.5, classified as grade D in the OK category. The 28.83-point increase demonstrates a significant improvement in user experience, moving from OK to excellent. Thus, it can be concluded that the redesign of the Diva Clinic website effectively enhances user experience, making the Diva Clinic website more effective and attractive to user.